Exploring Artificial Intelligence Governance in Higher Education: Policy Design, Implementation and Adaptability in Egypt - Eissa, Rolane (AUC Knowledge Fountain, 2026)
The rapid adoption of artificial intelligence (AI) in higher education (HE) underscores the need for effective governance frameworks that ensure ethical use and academic integrity. Despite increased policy attention, universities face significant challenges in translating AI governance (AIG) principles and policies into coherent, practical practices within complex organizational settings. Existing research on AIG remains conceptual and focused on the Global North. It offers limited empirical insight into how AI policies are interpreted and enacted at the institutional level, particularly in HE systems in the Global South. This study addresses these gaps by examining AIG in Egyptian universities, thereby providing empirically grounded evidence on its drivers, policy design, implementation, and adaptability within a specific HE context. Using a qualitative research design, the study draws on document analysis and semi-structured interviews with academics and administrators, guided by institutional isomorphism and policy enactment theories. The findings indicate that AIG in Egyptian universities is evolving and hybrid, shaped by global and national pressures yet constrained by limited enforcement mechanisms, uneven AI literacy, and reliance on individual professional judgment during implementation.